Ultrafast Dynamics of the Topological Semimetal GdSbxTe2-x-δ in the Presence and Absence of a Charge Density Wave - Kirby, Robert J.; Montanaro, Angela; Giusti, Francesca; Koch-Liston, Andre; Lei, Shiming; Petrides, Ioannis; Narang, Prineha; Burch, Kenneth S.; Fausti, Daniele; Scholes, Gregory D.; Schoop, Leslie M. (Journal of Physical Chemistry C, 2023)
Time-resolved dynamics in charge-density-wave materials have revealed interesting out-of-equilibrium electronic responses. However, these are typically only performed in a single material possessing a CDW. As such, it is challenging to separate subtle effects originating from the CDW. Here, we report on the ultrafast dynamics of the GdSbxTe2-x-δ series of materials where EF can be tuned, resulting in a change from an undistorted tetraganal phase to a CDW with a wavevector that depends on x. Using mid-infrared, near-infrared, and visible excitation, we find the dynamics are sensitive to both EF and the presence of the CDW. Specifically, as the Sb content of the compounds increases, transient spectral features shift to higher probe energies. In addition, we observe an enhanced lifetime and change in the sign of the transient signal upon removing the CDW with high Sb concentrations. Finally, we reveal fluence- and temperature-dependent photoinduced responses of the differential reflectivity, which provide evidence of transient charge density wave suppression in related telluride materials. Taken together our results provide a blueprint for future ultrafast studies of CDW systems.
CRIS-Team Scopus Importer:2023-01-27